Perancangan Dan Evaluasi Usability User Interface Aplikasi Cemilanpuas Berbasis Website - Iustisia Natalia Simbolon; Deny Ramadhan Pane; Aryanti Verina Putri Siregar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
User-centered design methods are used to identify user needs, analyze usage contexts, and design interfaces that are intuitive and easy to use. In this study, data collection was carried out through interviews with Cemilanpuas stakeholders and prospective users. Based on the data obtained, the researcher formulates user requirements and creates a solution design in the final form of a prototype. After the design is complete, usability evaluation is carried out using the Think Aloud method. Evaluators are directed to complete a series of tasks that represent common activities in using the Cemilanpuas application. During the test, the constraints and difficulties encountered by the evaluator were recorded both verbally and non-verbally. The results of the usability evaluation contain the advantages and disadvantages of the user interface which are grouped based on the five usability points. Based on these findings, improvements were made with a minimum of two iterations. Measuring the value of user satisfaction has a grade B final result of 87.5. This research makes an important contribution in understanding user needs and improving the usability of the website-based Cemilanpuas application. The results of this study can be used as a guideline for the development and improvement of the user interface of similar applications in the future.